2021
DOI: 10.1371/journal.pone.0258860
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive finance, industrial structure upgrading and farmers’ income: Empirical analysis based on provincial panel data in China

Abstract: This paper empirically studies the relationship among inclusive finance, industrial structure upgrading and farmers’ income, using the panel data of 28 provinces in China from 2006 to 2016.The research finds that inclusive finance can significantly promote the increase of farmers’ income. Moreover, the Upgrading of Industry Structure (UIS) is the intermediary mechanism of inclusive finance to promote the increase of farmers’ income, and this intermediary mechanism is heterogeneous among farmers with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Yu and Wang found that inclusive finance can reduce wage income, promote the growth of farmers' income, and narrow the income gap between urban and rural areas [15]. Liu et al found that inclusive finance promotes farmers' income growth through the mediating role of industrial structure upgrading, realizing the integration of farmers and modern agricultural industry through technological innovation in the process of industrial upgrading, and the modern agricultural industry is agriculture based on modern industry and modern science and technology [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Yu and Wang found that inclusive finance can reduce wage income, promote the growth of farmers' income, and narrow the income gap between urban and rural areas [15]. Liu et al found that inclusive finance promotes farmers' income growth through the mediating role of industrial structure upgrading, realizing the integration of farmers and modern agricultural industry through technological innovation in the process of industrial upgrading, and the modern agricultural industry is agriculture based on modern industry and modern science and technology [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Tanzania's number one objective in its list of sustainable development goals is to end poverty in all its displays [30]. Financial inclusion can significantly help farmers' incomes rise [31]. The growth of digital inclusive finance has considerably aided the modernization of the region's industrial structure and has a favorable overall impact on that modernization [32].…”
Section: Digital Inclusion Of Finance Alleviates Povertymentioning
confidence: 99%
“…Some villages have successfully explored innovative models of rural e-commerce in the form of collective economy, which has led to further expansion of the collective village economy while improving rural habitat conditions and infrastructure [6]. Research between rural e-commerce development and farming subjects has been more extensive, and scholars have not only found that individual characteristics such as prior experience [8], social capital [9], perceived value [10], information literacy [11] and risk preference [12] have significant effects on farming households' willingness to participate in e-commerce, participation behavior and participation level, but also there is a general consensus that participation in rural e-commerce can promote farming households' income growth [13][14][15][16], increased employment opportunities [16][17][18] and increased entrepreneurship, and the sense of entrepreneurship [19,20] formed a general consensus, which was confirmed by crosssectional or panel data from multiple provinces and regions. These studies show that rural e-commerce is not only an important force for promoting rural economic development, but also an important driving force for transforming traditional farmers into new farmers.…”
Section: Literature Reviewmentioning
confidence: 99%